Lignin-containing nanocelluloses (LNCs) as renewable and sustainable alternatives: Prospects, and challenges - Kumar A.; Sood A.; Maiti P.; Han S.S. (My University, 2025)
Lignin-containing nanocelluloses (LNCs) with adjustable lignin contents have shown much attention to be utilized in different industrial and biomedical applications due to their renewable and sustainable nanotechnology, remarkable characteristics. Therefore, there is a need to foster process technologies for producing lignin-containing nanocelluloses (LNCs), which are eco-friendly, cost-effective, sustainable, and can be utilized for wider industrial or biomedical applications. In this precise review, we provide an overview of fundamental challenges and opportunities in production of LNCs and their diverse end-use applications. © 2023 Elsevier B.V.